DAMPAK BULLYING TERHADAP POLA INTERAKSI SOSIAL SISWA DI SEKOLAH DASAR - Rahmayanti, Zuli; Zumrotun, Erna; Rofiqoh, Naili (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This research is motivated by the widespread issue of bullying in education, due to its negative impacts on individuals, the school environment, and school academics.This study examines the social phenomenon of bullying at Daren 2 Public Elementary School. This study used a qualitative method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation studies. Data analysis refers to the Miles and Huberman model, which includes three stages: data reduction, data presentation, and verification and conclusion drawing. The research findings revealed that verbal bullying, such as teasing, insults, and exclusion, still frequently occurs and has a negative impact on the social, psychological, and academic aspects of victims. The contributing factors are a quiet personality, lack of parental supervision, and unstable family conditions. The impacts experienced by victims include low self-confidence, trauma, fear of social interactions, and decreased academic achievement. Therefore, a school-based approach is needed through a bullying prevention program and synergy between parents and teachers in providing emotional support to create a conducive and inclusive learning environment.